ANALISIS YURIDIS MENGENAI PEMBUKTIAN INFORMASI DAN DOKUMEN ELEKTRONIK PADA SENGKETA PROSES PEMILIHAN UMUM DI PENGADILAN TATA USAHA NEGARA - Asnawi, Eddy; Libra, Robert (Fakultas Ilmu Sosial dan Humaniora, 2024)
The State Administrative Court has the authority to adjudicate General Election Process Disputes based on Perma No. 5/2017. Types of evidence in General Election disputes are: letters or writings, witness statements, expert statements, confessions of the parties, the judge's knowledge and other evidence in the form of electronic information or electronic documents. Meanwhile, in its development, this electronic document is known and considered as evidence in procedural legal processes, especially in the evidentiary stage. From this problem, the formulation of the problem raised is how to carry out a juridical analysis regarding the verification of electronic information and electronic documents in disputes over the general election process in the state administrative court based on Perma No. 5/2017. The research method used is normative juridical with a statutory approach. The results found that from a formal juridical perspective, the law of evidence in Indonesia, in this case the state administrative court procedural law, does not yet accommodate electronic documents as evidence. Meanwhile, several new laws have regulated and recognized electronic evidence as valid evidence. Then in Perma No. 5/2017 also mentions electronic information or electronic documents as a type of evidence for general election process disputes. The benchmark given by the judge in assessing electronic evidence in the trial of State Administrative disputes at the State Administrative Court is that as long as the judge uses two types of evidence as regulated in the Law, obtained legally and can be convincing then the judge can decide the case with those evidence.